The Effect of Knee Sleeve Use on The Agility of University Martial Arts Club Students - Sisybania; Fathi Muhammad (Poltekkes Kemenkes Jakarta I, 2026)
Background: The Health Polytechnic of the Ministry of Health Surakarta provides extracurricular programs to support students’ non-academic development, including the Martial Arts Student Activity Unit. Kicking techniques are the dominant component in martial arts and require high agility, defined as the ability to rapidly change direction to evade attacks and execute effective counterattacks. These movements involve repetitive loading of the knee joint, increasing the risk of overuse injury and decreased functional performance. Knee sleeves, made of elastic materials, provide compression and thermal support that may enhance joint function. Previous studies report benefits such as pain reduction, improved proprioception, and increased knee stability. Aims: To determine the effect of knee sleeve use on agility among students participating in the Martial Arts Student Activity Unit. Methods: A true-experimental study using a pre-test and pot-test control group design, in which participants were randomly allocated to groups, with a randomized controlled trial design was conducted involving 32 students, divided into experimental and control groups (n=16 each). Agility was measured using the T-Test. Data were analyzed using paired-sample t-tests to assess within-group pre-post changes and independent-sample t-tests to compare the experimental and control groups. Results: Agility improved in both groups after the intervention, but the improvement was significantly greater in the knee sleeve group than in the knee sock (control) group (p= 0.031), indicating that knee sleeve use provides an additional benefit for agility beyond that of standard knee socks. Conclusion: Knee sleeve use has a significant effect on improving agility and may help reduce the risk of overuse injuries during martial arts training. Keywords: Knee sleeve; Agility; Kicking